Ethnography Research in Real-Life Environment: A Case Study Based on Street Children in Mamaghar, Nepal, Hetauda - Risal, Nischal (Malaysian Journal of Business and Economics (MJBE), 2018)
The exploration of ethnography research in the street children of Hetauda is the major aim of the research paper. A case of Mamaghar Nepal has been adopted in the paper. The qualitative and inductive research approaches have been used in the ethnography research. An interview method is thought as suitable method to collect the secondary information from the concerned ethnographer Mr Arpan Parajuli. The paper concluded the great importance of ethnography research in real-life environment to overcome the current problem of the street children in Hetauda. The policy makers’ positive awareness in the policy on the street children issue was major outcome of the research. To understand the ethnography in Nepali context, the research paper is supposed to be the additional knowledge building paper for students, academicians, practitioners, professionals, authorities as well as researchers. Keywords: ethnography, street children, Mamaghar, case study, real-life environment